Factors associated with death from COVID-19 in traditional peoples and communities in Brazil. - Sebastião Bruno Taveira Silva; Audêncio Victor; Ana Raquel Ernesto Manuel Gotine; Dalva Maria de Assis; Marcelo Yoshito Wada; Greice Madeleine Ikeda do Carmo; Luciana Nogueira de Almeida Guimarães; Eucilene Alves Santana (PLoS ONE)
Introduction COVID-19 has disproportionately impacted vulnerable populations, including traditional communities in Brazil, who face socioeconomic and health disparities, increasing the risk of severe outcomes. This study aims to identify factors associated with mortality among hospitalized COVID-19 patients from traditional communities in Brazil. Methods This cross-sectional study analyzed data from the System of Epidemiological Surveillance of Influenza (SIVEP-Gripe) on hospitalizations for COVID-19 between 2021 and 2023. Individuals from traditional communities were included. The variables analyzed included demographic characteristics, clinical symptoms, comorbidities, and the need for hospital support. Logistic regressions were performed to assess associations with mortality, considering p < 0.05 significant. Results Of the 7,101 cases analyzed, males showed a higher risk of death (OR = 1.39; 95% CI: 1.18-1.63). Among ethnic groups, blacks presented with an OR = 2.92 (95% CI: 1.68-5.08) and indigenous, OR = 2.25 (95% CI: 1.73-2.94). Older age increased the risk, with OR = 6.57 (95% CI: 2.16-28.5) for ages 60-79 and OR = 12.8 (95% CI: 4.18-55.8) for ≥80 years. Dyspnea (OR = 2.16; 95% CI: 1.77-2.65) and low saturation (OR = 2.13; 95% CI: 1.78-2.55) were associated with death, while loss of taste was protective (OR = 0.62; 95% CI: 0.51-0.75). Immunosuppression (OR = 2.14; 95% CI: 1.23-3.79) and chronic renal disease (OR = 1.64; 95% CI: 1.10-2.46) increased the risk. Patients on invasive ventilation had the highest risk of death (OR = 19.4; 95% CI: 15.2-25.0), followed by non-invasive ventilation (OR = 2.65; 95% CI: 2.18-3.23) and ICU (OR = 2.15; 95% CI: 1.85-2.49). Conclusion Risk factors for mortality among hospitalized patients from traditional communities include male sex, older age, race/color, severe respiratory symptoms, comorbidities, and the need for invasive ventilation. These findings reinforce the importance of targeted health strategies to reduce the risk of mortality in these vulnerable populations.